2017
DOI: 10.1007/s11481-017-9766-1
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between Glia, Neurons and Mast Cells in Neuroinflammation Associated with Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a progressive movement disorder characterized by neuroinflammation and dopaminergic neurodegeneration in the brain. 1-methyl-4-phenylpyridinium (MPP+), a metabolite of the parkinsonian neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) induces the release of inflammatory mediators from glial cells and neurons. Glia maturation factor (GMF), a brain proinflammatory protein, MPP+, and mast cell-derived inflammatory mediators induce neurodegeneration which eventually leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 76 publications
3
40
0
Order By: Relevance
“…In addition, mast cells tended to surround ganglion cells, suggesting that mast cells are mediators of neuritis. These findings are consistent with evidence that mast cells mediate neurodegenerative diseases . Previous analysis of gene expression profiles in tissue samples of achalasia demonstrated that toll‐like receptor 4 and interleukin (IL)‐18 are key players involved in neuronal/muscular and neuronal/immunity processes .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, mast cells tended to surround ganglion cells, suggesting that mast cells are mediators of neuritis. These findings are consistent with evidence that mast cells mediate neurodegenerative diseases . Previous analysis of gene expression profiles in tissue samples of achalasia demonstrated that toll‐like receptor 4 and interleukin (IL)‐18 are key players involved in neuronal/muscular and neuronal/immunity processes .…”
Section: Discussionsupporting
confidence: 87%
“…These findings are consistent with evidence that mast cells mediate neurodegenerative diseases. 10 Previous analysis of gene expression profiles in tissue samples of achalasia demonstrated that toll-like receptor 4 and interleukin (IL)-18 are key players involved in neuronal/ muscular and neuronal/immunity processes. 35 Both proteins are significantly associated with mast cells in immunity diseases, further supporting our present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies have highlighted the role of MCs in brain neuroinflammatory responses, and our findings indicate that significant elevations of MC number and degranulation are associated with postoperative cognitive dysfunction through microglial activation [10]. In addition, altered MC degranulation has also been found in other CNS disorders, such as stroke [11], Parkinson's disease [12], and multiple sclerosis [13]. Microscopic investigations have also demonstrated infiltrated β-tryptase-containing MCs in human brains with amyloid deposits [14].…”
Section: Introductionmentioning
confidence: 53%
“…Further, we have shown that mast cells also express GMF and suggest that GMF in mast cells may also play an important role in the pathogenesis of neurodegenerative diseases including AD (Kempuraj et al, 2015 ). Additionally, we have also shown that GMF activates mouse and human mast cells to release mast cell specific proteases and other neuroinflammatory mediators that are implicated in neuroinflammation and neurodegeneration in PD and AD (Kempuraj et al, 2015 , 2017a ). We have previously reported enhanced expression of IL-33 and GMF at the vicinity of APs and NFTs in human AD brain (Xiong et al, 2014 ).…”
Section: Mast Cells Neuroinflammation and Admentioning
confidence: 96%